Un acercamiento engañoso: las relaciones políticas hispano-francesas entre 1958 y 1970 - Álvaro Fleites Marcos (Cahiers de Civilisation Espagnole Contemporaine)
General De Gaulle’s rise to Power in June 1958 led to a substantial improvement of Spanish-French relations, which included landmarks like the solution of the double problem of the refugees and the visits of members of the French government to Madrid, particularly that of the French Foreign minister Maurice Couve de Murville in may 1964. Paris also supported both the Spanish entry into the OEEC and its Common Market association application but it didn’t conceal Spain’s reduced role in the Gaullist foreign strategy, which aggravated the unbalanced relations between the two countries. This disproportion, the prevailing importance for the Spanish government of its links with the United States and the French distrust of the Franquist regime constituted unsurpassable limits of the bilateral relations in the period. It will be necessary to wait until the end of Franco’s regime to reach a true friendship and will to cooperate between the two sides of the Pyrenees.